Metacognitive Instruction Does Improve Listening Comprehension. (7th March 2012) - Bozorgian, Hossein
Abstract : This paper reports on a small-scale study, which looked into the impact of metacognitive instruction on listeners' comprehension. Twenty-eight adult, Iranian, high-intermediate level EFL listeners participated in a "strategy-based" approach of advance organisation, directed attention, selective attention, and self-management in each of four listening lessons focused on improving listeners' comprehension of IELTS listening texts. A comparison of pretest and posttest scores showed that the "less-skilled" listeners improved more than "more-skilled" listeners in the IELTS listening tests. Findings also supported the view that metacognitive instruction assisted listeners in considering the process of listening input and promoting listening comprehension ability.